Gender differences in factors associated with the health literacy of hospitalized older patients with chronic diseases: A cross-sectional study - Sun, Shuting; Lu, Jinjin; Wang, Yawen; Wang, Ya; Wu, Lihao; Zhu, Saiqiong; Zheng, Xiuyun; Lu, Xueqin; Xu, Hongbo (Frontiers in Public Health, 2022)
Background To identify gender differences in factors associated with the health literacy of hospitalized older patients with chronic diseases. Methods A total of 471 hospitalized older patients with chronic diseases in four hospitals were investigated from May 2019 to June 2020. The self-developed demographic information questionnaire, the “Health Literacy Scale for Patients with Chronic Diseases” and the “Self-Efficacy for Managing Chronic Diseases 6-item Scale” were applied in this study. Multiple linear regression was used to assess the factors influencing health literacy among older patients with chronic diseases by gender. Results The factors influencing health literacy differed by gender. Male health literacy was related to education background, number of children, monthly income, duration of chronic disease and chronic disease self-efficacy. For females, health literacy was associated with age, education background, monthly income, duration of chronic disease and chronic disease treatment. Conclusion Healthcare providers should focus on the above-mentioned factors that could help identify those with low health literacy differ base on gender. Gender-specific strategies should be developed to improve the health literacy of older patients with chronic diseases and strengthen their chronic disease management.